PENATAAN ESTABLISH SHOT PADA ROAD MOVIE ELEGI PANASEA UNTUK MEMPERKUAT RUANG DAN WAKTU - Zuardi, Jundila (Institut Seni Indonesia Padangpanjang, 2025)
The Elegi Panasea road movie has the theme of Raka's journey to the city of Singapore to look for his siblings. During the journey, Raka experiences several conflicts and finally meets his siblings. The establishing shot arrangement in the Road film Elegi Panasea functions to provide visual context and provide orientation to the audience regarding space and time. The creator as director of photography (DOP) determines technical aspects such as shot type, composition and camera movement to apply establish shots in several scenes such as the scene of Raka holding a debt settlement letter in a messy terrace condition. Establish shots play an important role in providing visual orientation to the audience understands the setting, atmosphere and time transitions, thus supporting the storyline and emotional experience. The creation of the fictional film Elegi Panasea aims to provide an illustration of not easily trusting people because crime can happen anywhere and at any time. The film Elegi Panasea teaches the importance of being careful in making decisions and reminds you of the importance of introspection and considering the consequences of actions